Practicing the politics of Jesus: the origin and significance of John Howard Yoder's social ethics - Zimmerman, Earl (The C. Henry Smith series, 2007)
Yoder rearranges the theological landscape -- North American Mennonite experience -- Amsterdam 1952 -- American church and society in the postwar era -- Mennonite mentors at Goshen College -- European experience and the debate about war -- A European assignment -- Relating to European Mennonite churches -- Confronting the moral question of war -- The world council of churches debate -- Doctoral studies with Barth and Cullman -- The theology of Karl Barth -- Oscar Cullmann and biblical studies -- Other European conversations -- Disseration on the Swiss anabaptists -- Historical anabaptist research -- The core of anabaptist beliefs -- Constructing an anabaptist theology -- Understanding the "politics of Jesus" -- Characterizing theologies -- Yoder's theological language -- Yoder's constructive theology -- A lived praxis -- The "politics of Jesus" as social practice -- The challenge of just peacebuilding -- Basic principles of the "politics of Jesus' -- A conversation with Catholic peace traditions -- Just peacebuilding collaboration -- The social praxis of the Christian community -- A religious peacebuilding program